Muhammad Syahrur's Thoughts on the Term Nisa' in the Al-Qur'an Surah Ali Imran: 14 (Hermeunetical Studies) - Syamsul Amri; Arifinsyah (al-Afkar, Journal For Islamic Studies, 2024)
Muhammad Syahrur, a renowned Islamic thinker in the contemporary era, has made significant contributions in this field. According to Syahrur, there is no need to stick to traditional interpretations in understanding the verses of the Koran. For example, in his analysis of QS. Ali-Imran: 14, he suggests that the word "nisa'" should not be translated literally as "adult woman" because it is not relevant to the current context. Syahrur's research uses a library research approach and utilizes semantic methods. He introduced the concept of la taradduf theory, which states that a word can have many meanings depending on the context of the verse. Syahrur emphasized the equality of women and men, rejecting the notion that women should be treated as objects of oppression or equated with inanimate objects.